Blockade of TGF-β signaling by the TGFβR-I kinase inhibitor LY2109761 enhances radiation response and prolongs survival in glioblastoma - Zhang, Mengxian; Kleber, Susanne; Röhrich, Manuel; Timke, Carmen; Han, Na; Tüttenberg, Jochen; Martín-Villalba, Ana; Debus, Jürgen; Peschke, Peter; Wirkner, Ute; Lahn, Michael; Huber, Peter E. (Cancer research, 2011)
Glioblastoma multiforme (GBM) is a highly aggressive primary brain tumor that tends to be resistant to the ionizing radiotherapy used to treat it. Because TGF-β is a modifier of radiation responses, we conducted a preclinical study of the antitumor effects of the TGF-β receptor (TGFβR) I kinase inhibitor LY2109761 in combination with radiotherapy. LY2109761 reduced clonogenicity and increased radiosensitivity in GBM cell lines and cancer stem-like cells, augmenting the tumor growth delay produced by fractionated radiotherapy in a supra-additive manner in vivo. In an orthotopic intracranial model, LY2109761 significantly reduced tumor growth, prolonged survival, and extended the prolongation of survival induced by radiation treatment. Histologic analyses showed that LY2109761 inhibited tumor invasion promoted by radiation, reduced tumor microvessel density, and attenuated mesenchymal transition. Microarray-based gene expression analysis revealed signaling effects of the combinatorial treatments that supported an interpretation of their basis. Together, these results show that a selective inhibitor of the TGFβR-I kinase can potentiate radiation responses in glioblastoma by coordinately increasing apoptosis and cancer stem-like cells targeting while blocking DNA damage repair, invasion, mesenchymal transition, and angiogenesis. Our findings offer a sound rationale for positioning TGFβR kinase inhibitors as radiosensitizers to improve the treatment of glioblastoma. Cancer Res; 71(23); 7155-67. ©2011 AACR.